2012
DOI: 10.1186/1471-2318-12-72
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a trunk release maneuver on Peak Pressure Index, trunk displacement and perceived discomfort in older adults seated in a high Fowler’s position: a randomized controlled trial

Abstract: BackgroundPressure ulcers pose significant negative individual consequences and financial burden on the healthcare system. Prolonged sitting in High Fowler’s position (HF) is common clinical practice for older adults who spend extended periods of time in bed. While HF aids in digestion and respiration, being placed in a HF may increase perceived discomfort and risk of pressure ulcers due to increased pressure magnitude at the sacral and gluteal regions. It is likely that shearing forces could also contribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…A0→A1→A2→A3→B1→B2), overall, mean and peak pressures increased, leading to users' uncomfortable experience. This result was consistent with previous body pressure studies of other furniture products 31 .…”
Section: Discussionsupporting
confidence: 94%
“…A0→A1→A2→A3→B1→B2), overall, mean and peak pressures increased, leading to users' uncomfortable experience. This result was consistent with previous body pressure studies of other furniture products 31 .…”
Section: Discussionsupporting
confidence: 94%
“…In this study, the interface pressure was calculated using two variables that indicated the strength and redistribution of pressure. The strength of pressure was identified using the peak pressure [ 26 , 27 ], and the redistribution of pressure was confirmed using the risk area ratio [ 28 ]. Using the XSENSOR X3 PX100 system (ForeSite SS Mattress System, XSENSOR Technology, Calgary, AB, Canada), we measured interface pressures in the subjects’ bony prominence sites.…”
Section: Methodsmentioning
confidence: 99%
“…We operationally defined total lying time as the period within 24 hours each day spent in horizontal or near-horizontal position (e.g., Fowler position 24 ) , semi-Fowler position 25 ) , not involving high-Fowler position 26 ) ) in spite of the presence or absence of sleeping, napping, receiving massage, watching television, listening to radio, and so on, regardless of purpose or location. Firstly, participants were asked to recall retrospectively the average time per day they spent horizontally lying in the previous week in increments of 30 minutes as follows: “How many hours per day did you typically spend lying with or without doing something like sleeping, napping, receiving massage, watching television, listening to radio, or other on a usual day, regardless of purpose or place in the previous week?” The question to measure total lying time is referred to in previous studies as the single question to measure total sitting time 15 ) and the definition of sedentary behavior 2 , 27 ) .…”
Section: Participants and Methodsmentioning
confidence: 99%